Air and environmental sampling for SARS-CoV-2 around hospitalized patients with coronavirus disease 2019 (COVID-19). (8th November 2020) - Cheng, Vincent Chi-Chung; Wong, Shuk-Ching; Chan, Veronica Wing-Man; So, Simon Yung-Chun; Chen, Jonathan Hon-Kwan; Yip, Cyril Chik-Yan; Chan, Kwok-Hung; Chu, Hin; Chung, Tom Wai-Hin; Sridhar, Siddharth; To, Kelvin Kai-Wang; Chan, Jasper Fuk-Woo; et al.
Abstract: Background: The role of severe respiratory coronavirus virus 2 (SARS-CoV-2)–laden aerosols in the transmission of coronavirus disease 2019 (COVID-19) remains uncertain. Discordant findings of SARS-CoV-2 RNA in air samples were noted in early reports. Methods: Sampling of air close to 6 asymptomatic and symptomatic COVID-19 patients with and without surgical masks was performed with sampling devices using sterile gelatin filters. Frequently touched environmental surfaces near 21 patients were swabbed before daily environmental disinfection. The correlation between the viral loads of patients' clinical samples and environmental samples was analyzed. Results: All air samples were negative for SARS-CoV-2 RNA in the 6 patients singly isolated inside airborne infection isolation rooms (AIIRs) with 12 air changes per hour. Of 377 environmental samples near 21 patients, 19 (5.0%) were positive by reverse-transcription polymerase chain reaction (RT-PCR) assay, with a median viral load of 9.2 × 10 2 copies/mL (range, 1.1 × 10 2 to 9.4 × 10 4 copies/mL). The contamination rate was highest on patients' mobile phones (6 of 77, 7.8%), followed by bed rails (4 of 74, 5.4%) and toilet door handles (4 of 76, 5.3%). We detected a significant correlation between viral load ranges in clinical samples and positivity rate of environmental samples ( P < .001). Conclusion: SARS-CoV-2 RNA was not detectable by air samplers, which suggests that the airborne route is not the predominant mode of transmission of SARS-CoV-2. Wearing a surgical mask, appropriate hand hygiene, and thorough environmental disinfection are sufficient infection control measures for COVID-19 patients isolated singly in AIIRs. However, this conclusion may not apply during aerosol-generating procedures or in cohort wards with large numbers of COVID-19 patients.